CONVERGENCE THEOREMS OF MONOTONE (, )-NONEXPANSIVE MAPPINGS FOR NORMAL-S ITERATION IN ORDERED BANACH SPACES WITH CONVERGENCE ANALYSIS - Muangchoo-in, K.; Kumam, P.; Yao, J. C.; Wen, C. F. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2020)
In this work, we prove some theorems of existence of fixed points for a monotone (α, β)-nonexpansive mapping in a uniformly convex ordered Banach space. Also, we prove some weak and strong convergence theorems of normal-S iteration under some control condition. Finally, we give two numerical examples to illustrate the main result in this paper.